1776 Pa. Laws 11, An Ordinance Respecting the Arms of Non-Associators, § 1 - (:unkn) unknown (General Publisher, 1776)
Authorized officers to collect all arms in the hands of “non associators”. -
--
Keywords: POSSESSION - DANGEROUS PERSONS